2017
DOI: 10.11114/jets.v5i7.2389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PDEODE Teaching Strategy on Turkish Students' Conceptual Understanding: Particulate Nature of Matter

Abstract: The aim of this study is to determine the effect of activities developed in accordance with PDEODE teaching strategy on students' understanding of the particulate nature of matter. The sample of the study consists of the first grade students who study in the Primary School Teacher Education Program. In order to determine the conceptual change on students a test consisting of 8 questions was applied to the sample. This test was applied as pre-test, post-test and delayed post-test. The difference between the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
(53 reference statements)
3
10
0
4
Order By: Relevance
“…For instance, one type of the enriched discussions with POE, i.e. PDEODE, where there were additions of discussions before and after the observation phase (Coştu, 2008;Coştu et al, 2010;2012;Demircioğlu, 2017) indicated similar results to another type of the enriched discussion with POE, i.e. PEODE, used in this research.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For instance, one type of the enriched discussions with POE, i.e. PDEODE, where there were additions of discussions before and after the observation phase (Coştu, 2008;Coştu et al, 2010;2012;Demircioğlu, 2017) indicated similar results to another type of the enriched discussion with POE, i.e. PEODE, used in this research.…”
Section: Discussionsupporting
confidence: 71%
“…In this respect, the whole POE-based approach made positive contributions to the development of scientific process skills. However, unlike the POE, the alternative method contributed to the fact that pre-service science teachers in the experimental group were inquired and pondered their thoughts by reviewing the different thoughts of the students in the experimental group (Coştu, 2008;Coştu et al, 2010;2012;Demircioğlu, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After observing the outcome of the demonstration, they return to their group to revise their explanations. This section of the lesson follows the Predict-Discuss-Explain-Observe-Discuss-Explain strategy (PDEODE) (Demircioglu, 2017) as students work in their small group of peers to build verbal scientific explanations based on their observations. Teacher questioning encourages them to apply the scientific ontological model to the observed phenomenon.…”
Section: The Thinking Frames Approachmentioning
confidence: 99%
“…Bu bakımdan literatüre fayda sağlanacağı düşünülmektedir. MTY'nin anlaşılması amacıyla birçok çalışma yürütülmüştür (Cengiz, 2018;Demircioğlu, 2017;Demircioğlu ve diğer., 2012;Jaber ve Boujaoude, 2012;Kırbulut ve Beeth, 2011;Kirman Bilgin, Demircioğlu Yürükel ve Yiğit, 2017;Naah ve Sanger, 2013;Özmen, 2011a;Philipp ve diğer., 2014;Smith ve Villareal, 2015). Bu çalışmaların birçoğunda kavram yanılgılarının değişime karşı dirençli olduğu ve yapılan uygulamalardan sonra da devam ettiği belirlenmiştir.…”
Section: Araştırmanın öNemiunclassified